The recurrence risk of gestational diabetes according to the number of abnormal values in the oral glucose tolerance test - Jenni Pukkila; Marja Vääräsmäki; Sanna Eteläinen; Sanna Mustaniemi; Hilkka Nikkinen; Mika Gissler; Tuija Männistö; Hannele Laivuori; Eero Kajantie; Elina Keikkala; the FinnGeDi Study Group (Acta Obstetricia et Gynecologica Scandinavica, 2025)
Abstract Introduction Oral glucose tolerance test (OGTT) results may be used to estimate the risk of recurrent gestational diabetes mellitus (GDM) in a subsequent pregnancy in the different study settings. This study assesses the association between the number of abnormal glucose values in the OGTT in the first pregnancy and GDM recurrence in a subsequent pregnancy in a Nordic cohort. Material and Methods This register‐based cohort study included 1677 women who had their first singleton delivery in 2009, underwent a 75 g 2‐h OGTT during the pregnancy, and gave birth at least once more within 10 years according to the Finnish Medical Birth Register. The cut‐off values were as follows: ≥5.3 mmol/L at fasting, ≥10.0 mmol/L at 1 h, and ≥8.6 mmol/L at 2 h. The odds ratio (OR) for GDM recurrence in the second pregnancy was analyzed via multivariable logistic regression adjusted for other potential factors associated with recurrence risk. Results During the first pregnancy, GDM was diagnosed in 331 (24.5%) women based on one (n = 250) or two or three (n = 81) abnormal glucose values in the OGTT. The total recurrence rate for GDM in the subsequent pregnancy was 56.2%. The rate differed significantly between women with one (51.6%) and women with two or three (70.4%) abnormal values in first‐pregnancy OGTT. Compared with those with normal OGTT results, the adjusted OR (aOR) for GDM in the subsequent pregnancy in women with one abnormal glucose value was 6.00 (95% CI, 4.34–8.30), while it was 13.37 (7.52–23.76) in women with two or three abnormal values. The odds for GDM recurrence among those with two or three abnormal glucose values was double compared to those with only one abnormal value (aOR 2.03, 1.12–3.68). Conclusions Primiparous women with one abnormal glucose value in the first OGTT have remarkable odds of GDM recurrence, with the odds doubling when there are two or three abnormal values during the first pregnancy. These findings can be used when planning effective counseling, prevention, and screening strategies for GDM in the subsequent pregnancy.